2021
DOI: 10.1002/slct.202100413
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Reduced ZnO/Ag Nanocomposites by a Green Microwave‐Assisted Method and Their Applications in Photodegradation of Methylene Blue Dye, and as Antimicrobial and Anticancer Agents

Abstract: In this present study, we report a facile microwave assisted green synthesis of ZnO/Ag nanocomposites (denoted as G‐ZnO/Ag NCs) by employing Tridax procumbens leaf extract as a green solvent for photocatalytic, antimicrobial and cytotoxicity activities. The prepared nanocomposites was characterized by various techniques to study its crystallinity, morphology, structure, chemical composition, optical properties, and so on. The nanocomposites exhibited excellent photocatalytic performance (90.2 %) toward methyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…As efficient scavengers for ˙OH, h + , and ˙O 2 − , respectively, isopropyl alcohol (IPA), disodium-EDTA, and para -benzoquinone (BZQ) have been employed to identify the primary active radical species participating in sunlight-driven deterioration process. 42,66 The photocatalytic reaction is observed to be suppressed by all scavengers; however, the scavenging capacity of the species is reduced in the order Na 2 -EDTA > BZQ > IPA. Using the scavengers IPA, BZQ, and Na 2 -EDTA, the percentage photocatalytic degradation of AzB was determined to be 77.8%, 48.4%, and 28%, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As efficient scavengers for ˙OH, h + , and ˙O 2 − , respectively, isopropyl alcohol (IPA), disodium-EDTA, and para -benzoquinone (BZQ) have been employed to identify the primary active radical species participating in sunlight-driven deterioration process. 42,66 The photocatalytic reaction is observed to be suppressed by all scavengers; however, the scavenging capacity of the species is reduced in the order Na 2 -EDTA > BZQ > IPA. Using the scavengers IPA, BZQ, and Na 2 -EDTA, the percentage photocatalytic degradation of AzB was determined to be 77.8%, 48.4%, and 28%, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This fast recovery is essential for its practical use in the further utilization of photocatalyst. 66…”
Section: Vsm Analysismentioning
confidence: 99%
“…Many studies have been conducted to prove the cytotoxicity potential of ZnO-Ag and ZnO NPs in reducing cancer progression. [65][66][67] Saranya et al created ZnO and Ag-ZnO NPs and evaluated them against the A549 cancer cell line, and they found that their product has cytotoxic ability over the A549 cell line. 67 Selvan et al utilized green synthesis techniques to generate Ag/ZnO nanocomposites and evaluated their anticancer efficacy on multiple cancer cell lines, including breast (MCF-7 and MDA-MB-231), colon (HCT-15), and lung (A549) cells.…”
Section: Resultsmentioning
confidence: 99%
“…[65][66][67] Saranya et al created ZnO and Ag-ZnO NPs and evaluated them against the A549 cancer cell line, and they found that their product has cytotoxic ability over the A549 cell line. 67 Selvan et al utilized green synthesis techniques to generate Ag/ZnO nanocomposites and evaluated their anticancer efficacy on multiple cancer cell lines, including breast (MCF-7 and MDA-MB-231), colon (HCT-15), and lung (A549) cells. Using the MTT assay, the researchers found that their product had signicant anticancer potential against all tested cancer cell lines tested.…”
Section: Resultsmentioning
confidence: 99%
“…The crystalline nature of the ZnO photocatalyst is reflected in the broadness of a peak, and the absorption band at 2333.83 cm -1 is created by the asymmetric and symmetric stretching mode vibrations of an air-absorbed CO 2 molecule [9]. Also, the wide peak at 3419.97 cm -1 and 1378.07 cm -1 , 1553.14 cm -1 may be due to stretching and bending vibrations of-OH group absorbed from the environment on the surface of the catalyst during FTIR measurement [10].…”
Section: Vibrational Spectroscopymentioning
confidence: 98%